The influence of lubricant on temperature generated in elasto-hydrodynamic contacts. - Cann,PM; Spikes,HA (Tribology Series, 1987)
Direct measurement of temperatures generated in concentrated contacts by infra-red (IR) radiometry can be used to explore the rheological properties of lubricants under elastohydrodynamic (EHD) conditions. This paper describes the influence of lubricant composition on thermal effects in EHD and attempts to relate rheological characteristics of the fluids to the temperature produced. The lubricants have been chosen to provide a range of rheological and chemical properties. They include synthetic hydrocarbons, polyglycols, perfluorethers, and a traction fluid. An emission technique similar to that employed by Winer and coworkers (1976) has been used to measure the surface temperature distribution within an EHD contact. Significant differences have been found between the surface temperature response of these fluids. The role of lubricant rheology in determining temperature with EHD contacts is discussed together with the implications of such measurement in the study of the traction response of lubricants.